The NSAID sulindac is chemopreventive in the mouse distal colon but carcinogenic in the proximal colon. Issue 3 (27th October 2010) - Mladenova, Dessislava; Daniel, Joseph J; Dahlstrom, Jane E; Bean, Elaine; Gupta, Ruta; Pickford, Russell; Currey, Nicola; Musgrove, Elizabeth A; Kohonen-Corish, Maija R J
Abstract : Background and aims: The non-steroidal anti-inflammatory drug sulindac is an effective chemopreventive agent in sporadic colorectal cancer but its potential benefit in mismatch repair deficient cancers remains to be defined. We wanted to determine whether genetic defects that are relevant for colorectal cancer, such as Msh2 or p53 deficiency, would influence the efficiency of sulindac chemoprevention or increase the side effects. Methods: Msh2 or p53 deficient and wild-type mice received feed containing 160–320 ppm sulindac for up to 25 weeks with or without a concurrent treatment with the carcinogen azoxymethane. Colon tissue was analysed by histopathology and molecular biology methods. Results: We show that sulindac prevented azoxymethane-induced distal colon tumours in all mice. In the proximal colon, however, sulindac induced new inflammatory lesions on the mucosal folds, which further developed into adenocarcinoma in up to 18–25% of the p53 or Msh2 deficient mice but rarely in wild-type mice. This region in the proximal colon was characterised by a distinct profile of pro- and anti-inflammatory factors, which were modulated by the sulindac diet, including upregulation of hypoxia inducible factor 1α and macrophage inflammatory protein 2. Conclusions: These data show that the sulindac diet promotes carcinogenesis in the mouse proximal colon possibly through chronic inflammation. Sulindac has both beneficial and harmful effects in vivo, which are associated with different microenvironments within the colon of experimental mice. Deficiency for the Msh2 or p53 tumour suppressor genes increases the harmful side effects of long-term sulindac treatment in the mouse colon.